The press on the web (Journal of Parents and Teachers, 2014)
The article lists the best-known newspapers that can now be found on the Internet.Among them are, for example, ABC, which is not only committed to the press, but also offers a wide variety of thematic content on its website, as well as El Pais, which also offers special supplements, including one dedicated to education.
Keywords: press; newspapers; digitisation